Transcriptional activating regions target attached substrates to a cyclin-dependent kinase - Ansari, Aseem Z. (National Academy of Sciences, 2005)
The yeast cyclin-dependent kinase Srb10 phosphorylates various transcriptional activators as they activate transcription, and acidic transcriptional activating domains found on several activators directly bind Srb10. Here we show that the interaction between Srb10 (with its associated cyclin Srb11) and each of several different activating regions, in vitro, leads to the phosphorylation of peptide sequences attached to but outside of the activating regions themselves. In some cases, residues within the activating regions are also phosphorylated. The results define a mechanism by which a kinase is recruited to alternate substrates with diverse physiological consequences.